Geospatial decision support system for ameliorating adverse impacts of irrigated agriculture on aquatic ecosystems - Fields, Christopher Michael, author; Labadie, John, advisor; Johnson, Lynn, advisor; Gates, Timothy, committee member; Hoag, Dana, committee member (Colorado State University. Libraries, 2019)
Although irrigation is key to the success of agriculture in much of the western United States, the associated water resource demands are often at odds with the needs of aquatic ecosystems. The storage and redistribution of natural water supplies that is required to meet agricultural demands often disturbs the natural streamflow regime that is key to the stream ecosystem. In many cases the conflicts between agricultural and ecological demands have led to increased regulatory restrictions on agricultural diversions to protect instream flows. While the results of such policies can help mitigate the most severe impacts of stream diversions, these regulations often result in agricultural shortfalls while achieving suboptimal environmental benefits. The Russian River basin in northern coastal California is a prime example of a region that is facing the challenges created by the often-disparate needs of agricultural and environmental interests. As the primary agricultural activity in the basin, wine grape cultivation is the largest water user in the basin with spring frost protection and summer irrigation constituting the bulk of those demands. At the same time, the Russian River and its tributary system have been identified by the U.S. Fish & Wildlife Service as critical habitat for the endangered coho salmon and the threatened Chinook salmon and steelhead trout, which rely on the highly stochastic and seasonal natural streamflow patterns of the system to support their life cycles. To reduce disruption of the natural streamflow regime and protect instream flows in the critical habitat, the California State Water Resources Control Board (SWRCB) has imposed a series of regulations that limit diversions. While a variety of studies in the Russian River basin have focused on the impacts of tributary diversions on instream flows as well as the effects of environmental regulations on streamflows and agricultural security, there is a lack of research that incorporates hydrometeorological modeling into such studies. To address this research gap and further study the effects of agricultural diversions and environmental regulations, a geospatial decision support system (geo-DSS) that combines a gridded hydrometeorological streamflow model (HL-RDHM) with a GIS-based river basin management model (GeoMODSIM) was developed and applied within the Russian River basin. In a proof-of-concept implementation, the geo-DSS is first applied to a representative tributary in the Russian River basin that has been categorized as critical fisheries habitat and supports viticulture. The geo-DSS incorporates unimpaired flow estimates from the fine-scale (1/4 HRAP or approx. 1km) gridded HL-RDHM model with GeoMODSIM, which evaluates water management impacts and uses a one-day timestep. The resulting model implementation is used to evaluate current agricultural water management practices, the effects of environmental regulations, and agricultural water management alternatives in the basin. The geo-DSS was shown to accurately represent the impacts of short-term spring frost protection demands and the continuing impacts through the summer irrigation season on instream flows, which can be detrimental to the threatened and endangered (TES) fish species in the region. Additionally, the implementation of minimum bypass flow environmental protections was shown to severely limit agricultural water supply. Finally, model results indicate that through the use of improved agricultural water management practices, such as off-stream ponds, overall system supplies are adequate to meet agricultural demands while satisfying environmental instream flow restrictions. In a second study, the geo-DSS was applied on a larger scale to the Feliz Creek tributary system in the upper Russian River basin to assess baseline conditions that included appropriated water rights, minimum bypass flow restrictions, existing agricultural pond storage, and agricultural demands. The baseline model framework was run with 100 sets of hydrologic forcing data to assess system performance across a variety of hydrologic conditions that ranged from dry to wet. Baseline results indicate that even with environmental restrictions in place, the cumulative impacts of upstream diversions can still be significant during low flow periods and agricultural supply shortfalls were common throughout the system. In subsequent scenarios agricultural management alternatives were evaluated to improve overall system performance. Results of these scenarios demonstrate that the addition of supplemental agricultural pond storage can significantly reduce agricultural supply shortages while making significant improvements to instream flow conditions. Additionally, the allowance of carryover storage from year to year, which is currently restricted in the basin, was shown to result in even more significant improvements. Finally, the model was used to identify the optimal location and size of supplemental storage within the basin. Overall, this type of tool is key to achieving the environmental instream flow goals in the Russian River basin while maintaining and enhancing the agricultural industry of the region.
Keywords: geographic information systems; stream ecosystems; decision support system; water management; irrigated agriculture